Interaction between bacterial endophytes and host plants - Mushtaq, Sehrish; Shafiq, Muhammad; Tariq, Muhammad Rizwan; Sami, Adnan; Nawaz-ul-Rehman, Muhammad Shah; Bhatti, Muhammad Hamza Tariq; Haider, Muhammad Saleem; Sadiq, Saleha; Abbas, Muhammad Taqqi; Hussain, Mujahid; Shahid, Muhammad Adnan (Frontiers in Plant Science, 2023)
Endophytic bacteria are mainly present in the plant's root systems. They improve plant health and are sometimes necessary to fight against adverse conditions. There is an increasing trend for the use of bacterial endophytes as bio-fertilizers. However, new challenges are also arising regarding the management of these newly discovered bacterial endophytes. Plant growth-promoting bacterial endophytes exist in a wide host range as part of their microbiome, and are proven to exhibit positive effects on plant growth. Endophytic bacterial communities within plant hosts are dynamic and affected by abiotic/biotic factors such as soil conditions, geographical distribution, climate, plant species, and plant-microbe interaction at a large scale. Therefore, there is a need to evaluate the mechanism of bacterial endophytes' interaction with plants under field conditions before their application. Bacterial endophytes have both beneficial and harmful impacts on plants but the exact mechanism of interaction is poorly understood. A basic approach to exploit the potential genetic elements involved in an endophytic lifestyle is to compare the genomes of rhizospheric plant growth-promoting bacteria with endophytic bacteria. In this mini-review, we will be focused to characterize the genetic diversity and dynamics of endophyte interaction in different host plants.